he Implementation of Scientific Learning Approach Six Thinking Hats Model to Enhance Studentsâ Thematic Learning Quality for The 5th Grader of Elementary School - Wijayanti, Rina; Gipayana, Muhana; Muhardjito, Muhardjito (Graduate School of Universitas Negeri Malang, 2018)
Abstract: Implementation of scientific learning approach six thinking hats model to enhance students thematic learning quality for 5th grader of elementary school, this research aims to (1) describe the implementation of scientific approach STH (six thinking hats) model that can enhance thematic learning quality, (2) enhance the learning quality in âEnvironment is Our Friendâ theme. This Classroom Action Research was conducted in two cycles. The subject of this research is A-class of 5th graders of Ngijo 3 Elementary School, Karangploso, Malang. The research result shows that implementation of STH model on thematic learning in 5th graders optimize the studentsâ learning quality. Implementation of STH model can improve discussion process by hat activity that combined with 5M (observing, questioning, reasoning, practicing, concluding) ability, also the learning outcome including studentsâ affective, cognitive, psychomotor ability.Abstrak: Penerapan pendekatan pembelajaran saintifik model Six Thinking Hats untuk meningkatkan kualitas pembelajaran tematik siswa kelas V SD, penelitian ini bertujuan untuk (1) mendeskripsikan penerapan pendekatan saintifik model STH (six thinking hats) yang dapat meningkatkan kualitas pembelajaran tematik, (2) meningkatkan kualitas pembelajaran pada tema âLingkungan Sahabat Kitaâ. Penelitian model tindakan kelas ini dilakukan dua siklus. Subjek penelitian siswa kelas VA SDN Ngijo 03 Karangploso, Kabupaten Malang. Hasil penelitian menunjukkan bahwa penerapan model STH dalam pembelajaran tematik di kelas V dapat mengoptimalkan kualitas belajar siswa. Penerapan model STH dapat meningkatkan proses berdiskusi dengan aktivitas yang dipadukan dengan kemampuan 5M (mengamati, menanya, menalar, mencoba, menyimpulkan), serta hasil belajar meliputi kemampuan afektif, kognitif, dan psikomotor siswa.